Study of Cultural Preservation and Protection of Cultural Values through Ethnocentricity of Domestic Products - Suryowati, Budi (Universitas Ibn Khaldun Bogor, 2023)
Globalization influences people's behavior in aspects of life. Changes in people's behavior include lifestyle, one of which is the desire to use foreign products. This research wants to find out how ethnocentric consumers are among Trilogi Uni-versity students, which totals 2,289 students. To assess consumer ethnocentrism using CETSCALE as a measure. Using the Structural Equation Modeling (SEM) method, the results of the study show that their opinions on ethnocentric in the form of protectionism, socio-economic conservatism, and ultra-nationalism affect unwillingness to buy foreign products, and opinions on na-tionalism do not affect unwillingness to buy foreign products